2016
DOI: 10.1016/j.cmi.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Post-invasion events after infection with Staphylococcus aureus are strongly dependent on both the host cell type and the infecting S. aureus strain

Abstract: Host cell invasion is a major feature of Staphylococcus aureus and contributes to infection development. The intracellular metabolically active bacteria can induce host cell activation and death but they can also persist for long time periods. In this study a comparative analysis was performed of different well-characterized S. aureus strains in their interaction with a variety of host cell types. Staphylococcus aureus (strains 6850, USA300, LS1, SH1000, Cowan1) invasion was compared in different human cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
152
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(168 citation statements)
references
References 30 publications
7
152
1
1
Order By: Relevance
“…Whereas several earlier studies have described the capacity of S. aureus to persist inside human cells, including non-professional phagocytes such as endothelial cells, other studies clearly showed the extreme propensity of this pathogen to rapidly kill infected cells (Loffler et al, 2014; Jubrail et al, 2016; Strobel et al, 2016). These apparent discrepancies are likely due the heterogeneity of protocols used to infect cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas several earlier studies have described the capacity of S. aureus to persist inside human cells, including non-professional phagocytes such as endothelial cells, other studies clearly showed the extreme propensity of this pathogen to rapidly kill infected cells (Loffler et al, 2014; Jubrail et al, 2016; Strobel et al, 2016). These apparent discrepancies are likely due the heterogeneity of protocols used to infect cells.…”
Section: Resultsmentioning
confidence: 99%
“…Initially classified as strict extracellular pathogen, S. aureus is now considered as a non-classical facultative intracellular pathogen (Sendi and Proctor, 2009). Indeed, numerous cell types can ingest S. aureus and the bacterium is able to persist within these cells for quite variable periods of time (Fraunholz and Sinha, 2012; Strobel et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus invades a variety of non‐professional phagocytic cells (NPPC): epithelial and endothelial cells, osteoblasts, fibroblast, keratinocytes, and others (see, for instance, Strobel et al, ; Horn, Stelzner, Rudel, & Fraunholz, ). Internalised S .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that the formation of autophagosomes facilitates the replication of S aureus in bovine mammary epithelial cells . The survival strategies of the pathogen are as diverse as strains or host cell types used . Although reports on S aureus and autophagy are increasing, none proves whether S aureus escapes or subverts autophagy in bovine macrophages.…”
Section: Introductionmentioning
confidence: 99%